2021
DOI: 10.1007/s11482-021-10003-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Residents' Leisure Time Allocation Mode on Individual Subjective Well-being: The Case of China

Abstract: As the main tension in Chinese society has become that between people's growing need for a better life and unbalanced and inadequate development, leisure activities have become a main factor affecting the subjective well-being of Chinese residents. This study uses micro data from the 2019–2020 Chinese Residents’ Economic Life Survey as the sample, applies the latent class analysis (LCA) method to conduct a joint analysis of all leisure activities of individuals, and then divides individual leisure time modes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…Furthermore, numerous research has demonstrated that regular physical activity, such as walking ( 51 ), could bring about array of benefits on an individual's physical and mental health, resulting in a relaxed and content state of mind and body. Meta-analysis of leisure sports participation and subjective wellbeing suggested that the leisure domain is an essential target for boosting subjective wellbeing ( 52 ), which has been demonstrated in the Chinese ( 53 ) and European ( 54 ) population. Mass sports activity is a form of leisure physical activity in which individuals of all ages can participate at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous research has demonstrated that regular physical activity, such as walking ( 51 ), could bring about array of benefits on an individual's physical and mental health, resulting in a relaxed and content state of mind and body. Meta-analysis of leisure sports participation and subjective wellbeing suggested that the leisure domain is an essential target for boosting subjective wellbeing ( 52 ), which has been demonstrated in the Chinese ( 53 ) and European ( 54 ) population. Mass sports activity is a form of leisure physical activity in which individuals of all ages can participate at any time.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of subjective well-being depends on the subjective experience of the subjects, rather than the standards of the outside world and others, which distinguishes it from the traditional clinical psychology. 9 A harmonious and happy family atmosphere can make people's subjective well-being stronger. On the contrary, the subjective well-being of single parent families and families with contradictions will be relatively weak.…”
Section: The Connotation Of College Students' Subjective Well Beingmentioning
confidence: 99%
“…Ibu yang memiliki anak usia sekolah membutuhkan banyak waktu untuk mengasuh. Menurut Wang et al (2022), penggunaan waktu ibu dalam mengalokasikan waktu luang kesehariannya bergantung pada banyaknya aktivitas yang dilakukan di rumah. Mengasuh dan merawat anak membutuhkan alokasi domestik yang tinggi sehingga mengurangi alokasi waktu personal dan leisure ibu (Ma & Piao, 2019).…”
Section: Pembahasanunclassified